Biased thermohaline exchanges with the Arctic across the Iceland–Faroe Ridge in ocean climate models - S. M. Olsen; B. Hansen; S. Østerhus; D. Quadfasel; H. Valdimarsson (Ocean Science, 2016)
The northern limb of the Atlantic thermohaline circulation and its transport of heat and salt towards the Arctic strongly modulate the climate of the Northern Hemisphere. The presence of warm surface waters prevents ice formation in parts of the Arctic Mediterranean, and ocean heat is directly available for sea-ice melt, while salt transport may be critical for the stability of the exchanges. Through these mechanisms, ocean heat and salt transports play a disproportionally strong role in the climate system, and realistic simulation is a requisite for reliable climate projections. Across the Greenland–Scotland Ridge (GSR) this occurs in three well-defined branches where anomalies in the warm and saline Atlantic inflow across the shallow Iceland–Faroe Ridge (IFR) have been shown to be particularly difficult to simulate in global ocean models. This branch (IF-inflow) carries about 40 % of the total ocean heat transport into the Arctic Mediterranean and is well constrained by observation during the last 2 decades but associated with significant inter-annual fluctuations. The inconsistency between model results and observational data is here explained by the inability of coarse-resolution models to simulate the overflow across the IFR (IF-overflow), which feeds back onto the simulated IF-inflow. In effect, this is reduced in the model to reflect only the net exchange across the IFR. Observational evidence is presented for a substantial and persistent IF-overflow and mechanisms that qualitatively control its intensity. Through this, we explain the main discrepancies between observed and simulated exchange. Our findings rebuild confidence in modelled net exchange across the IFR, but reveal that compensation of model deficiencies here through other exchange branches is not effective. This implies that simulated ocean heat transport to the Arctic is biased low by more than 10 % and associated with a reduced level of variability, while the quality of the simulated salt transport becomes critically dependent on the link between IF-inflow and IF-overflow. These features likely affect sensitivity and stability of climate models to climate change and limit the predictive skill.